1999
DOI: 10.1152/ajpregu.1999.277.3.r734
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of mouse prostaglandin transporter PGT cDNA: species-specific substrate affinities

Abstract: We recently identified and/or cloned the PG transporter PGT in the rat (rPGT) (Kanai, N., R. Lu, J. A. Satriano, Y. Bao, A. W. Wolkoff, and V. L. Schuster, Science 268: 866–869, 1995) and the human (hPGT) (Lu, R., and V. L. Schuster, J. Clin. Invest. 98: 1142–1149, 1996). Here we have cloned and expressed the mouse PGT (mPGT) cDNA. The tissue distribution of mPGT mRNA expression is significantly more restricted than that of rPGT and hPGT mRNA. Although the deduced amino acid sequence of mPGT is similar to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 25 publications
2
27
0
1
Order By: Relevance
“…PGE 2 is a substrate of MRP4, Oat3, and Pgt, which were reported to be expressed at the BBB (Pucci et al, 1999;Reid et al, 2003;Nilwarangkoon et al, 2007). We recently found that the protein expression level of MRP4 in mouse brain capillaries is 10.3 to 12.5% of that of P-glycoprotein, 33.1 to 39.6% of that of breast cancer resistance protein, and similar to that of Oat3 protein (Kamiie et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…PGE 2 is a substrate of MRP4, Oat3, and Pgt, which were reported to be expressed at the BBB (Pucci et al, 1999;Reid et al, 2003;Nilwarangkoon et al, 2007). We recently found that the protein expression level of MRP4 in mouse brain capillaries is 10.3 to 12.5% of that of P-glycoprotein, 33.1 to 39.6% of that of breast cancer resistance protein, and similar to that of Oat3 protein (Kamiie et al, 2008).…”
Section: Discussionmentioning
confidence: 94%
“…They can also be carried across membranes by a PG transporter (PGT; Kanai et al, 1995;Pucci et al, 1999). The finding that PGT is expressed in cell types that synthesize and release PGs may suggest that the transporter is involved in the re-uptake of PGs, either as a way of negating their leakage and/or facilitating the transport of such molecules to target nuclear receptors (Bao et al, 2002).…”
Section: Prostanoid Biosynthetic Pathways In Mammalsmentioning
confidence: 99%
“…PGT is broadly expressed in many cell types (Kanai et al, 1995;Lu et al, 1996;Pucci et al, 1999a). The strong expression of PGT in the lung suggests that PGT may play a role in the single-pass metabolic clearance of PGs through that vascular bed.…”
mentioning
confidence: 99%